The Influence Of Organizational Culture, Professional Competence And Motivation On Teacher Performance - Khalili, Khalili; Marwan, Marwan; Herayanti, Herayanti (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to analyze the influence of organizational culture, professional competence, and motivation on teacher performance in junior high schools in Jeunieb Subdistrict, Bireuen Regency. The research is motivated by the underutilization of the Merdeka Mengajar Platform (PMM) in rural areas, highlighting the need for a holistic approach to enhance teacher performance. Using a quantitative method with an explanatory survey design, data were collected from 145 teachers through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate that both organizational culture and professional competence significantly influence teacher motivation, which in turn directly affects performance. The indirect effects via motivation were stronger than direct effects. Motivation emerged as a key mediating factor linking institutional and personal variables to improved PMM engagement. The findings underscore the importance of fostering a supportive work environment, strengthening professional capacity, and enhancing intrinsic motivation to promote meaningful engagement in technology-based professional development.